Visitor's evaluation on facilities and services using importance-performance analysis at Sarawak cultural village - Abi, Jane; Mariapan, Manohar; Aziz, Azlizam (International Organization of Scientific Research, 2015)
Sarawak has been the popular cultural tourism attractions in Malaysia. The multi-racial and cultural Sarawak has the potential to develop cultural tourism and offers cultural experiences to local and foreign visitors. Sarawak Cultural Village (SCV) is one of the most visited sites at Sarawak. The cultural village provided various facilities and services to enrich visitor’s cultural experiences. The main objective of this study is to evaluate the facilities and services provided at SCV. The evaluation based on visitor’s opinion on the importance and performance rating of the listed attributes. About 300 questionnaires were distributed to the visitors to the cultural village during weekdays and weekends, public and school holidays. The socio-demographic data were evaluated using Frequency Analysis. The data showed the different socio-demographic, socio-economic, and trip characteristics of the visitors. The demographic and trip characteristics data provided the information of visitor’s motivation and preference activity during their visit to SCV. The Importance-Performance Analysis (IP Analysis) was used to evaluate the overall facility and service attributes, and the final result has been translated into Importance-Performance action grid. The action grid showed all the 22 attributes of general and specific facilities, and services provided were plotted on the High Importance and Performance quadrant. Attributes plotted on the action grid showed that all of the attributes were evaluated high on importance and performance suggested that the cultural village management should maintain the status of performance in all attributes area. The Ratio Analysis indicated the ranking of priority which needed special attention from the management of SCV. From the analysis, hospitality (service), Chinese Farm House (specific facility), and Penan Hut (specific facility) were ranked at the highest priority and needed special intention from the management. Overall, the result of the study was, all of the attributes were evaluated as High Importance and High Performance. The management of the SCV has to keep up the good work and maintain these attributes. Hopefully, the findings of this study will be useful for the management of SCV to manage and maintain the facilities and services provided to enhance the quality of visitors’ experiences.